Game Sains Pemanfaatan Barang Bekas menjadi Alat Sederhana IPA sebagai Media Belajar Siswa SMP selama Pandemi - Rina Rahayu; Riva Ismawati (Universitas Semarang, 2023)
Many used goods that are not utilized can contribute to the production of more and more waste. Students at partner schools are not used to using used materials for science learning media. This causes students to be unable to apply theory in science in everyday life which makes students' scientific literacy in partner schools still lacking. The difficulties of students in partner schools in learning science are possible because students do not know scientific phenomena that occur in everyday life and students are not introduced to science practices. Through the management of used goods into simple science tools, it is hoped that they can be used as learning media for students in partner schools. The method used in this activity is lecture, discussion, and practice. This activity was carried out for 3 meetings at each partner. These activities included delivering materials and making simple science teaching aids using used materials. Making simple science tools from used goods makes students learn about science. It also teaches students to take advantage of used goods in the surrounding environment, so that indirectly they can also maintain the environmental sustainability. The obstacle found in this activity was the limited time needed to make science teaching aids.